Formula Optimization of Feminine Liquid Soap from Garlic (Allium sativum Linn) Extract - Ingenida Hadning; Astri Yunika (Universitas Muhammadiyah Yogyakarta, 2021)
Leucorrhoea is a condition frequently experienced by women. If it is not appropriately treated, it can become a more severe problem. Leucorrhoea is caused by “Candida albicans” fungus infection. Garlic (Allium sativum Linn) has antibacterial and antifungal activity, where garlic can inhibit the growth of the Candida albicans. This study aims to determine the optimal formulation of feminine liquid soap from garlic extract (Allium sativum Linn) with good physical quality; thus, garlic in treating Leucorrhoea can be practically easier. Optimization of liquid soap formulation used carbopol and sodium lauryl sulfate with various concentration variations. The method included organoleptic observation, pH, and specific gravity for one-month storage to obtain a good physical quality of liquid soap. The result showed that the formula with 10% sodium lauryl sulfate met the physical quality test requirements of feminine liquid soap; thus, the formulation of feminine liquid soap with 10% sodium lauryl sulfate was optimal.